PENDIDIKAN KARAKTER BERBASIS TRI HITA KARANA DALAM TRADISI MENJOR DI DESA PADANGAJI, SELAT, KARANGASEM - Widiantana, I Kadek; Sutajaya, I Made; Suja, I Wayah (Guna Widya: Jurnal Pendidikan Hindu, 2024)
The menjor tradition is not only a religious symbol, but also has values contained in it. So far, this tradition has only been limited to complementing the ceremony, without knowing the essence contained in it. This research was conducted in Padangaji Village, Selat, Karangasem, using ethnographic methods to understand how the menjor tradition developed and adapted to social and economic changes associated with the Tri Hita Karana philosophy. In the context of Tri Hita Karana, the menjor tradition reflects a harmonious relationship with God through divine symbols. In the pawongan aspect, the menjor tradition involves community mutual cooperation, strengthening social ties, fostering unity, and building a sense of togetherness in the community. In the palemahan aspect, the use of natural materials such as bamboo, coconut leaves and plawa in making penjor shows concern for nature conservation. In an ecological context, plants such as bamboo and palm oil have an important role in preventing soil erosion and maintaining environmental sustainability. When the community still retains the materials for making penjor from the surrounding environment, it will certainly have positive implications for the ecosystem in the area. Character education is reflected in the Menjor tradition, where religious values, social solidarity and environmental concern are instilled through the implementation of this tradition